The Changing Boundaries of Journalistic Objectivity: Hybrid Journalism, Standpoint Theory, and Editorial Ethics in Poland - Jupowicz-Ginalska, Anna; Gober, Greta (Roczniki Nauk Społecznych, 2025)
The concept of journalistic objectivity has undergone scrutiny in recent years. Traditionally regarded as a cornerstone of journalistic integrity, it is increasingly critiqued as an outdated standard that fails to reflect the complexities of contemporary societies. Nowhere is this debate more evident than in Poland, where polarization, government interference, and declining press freedom fuel skepticism about neutrality. At the same time, efforts to promote inclusivity challenge dominant narratives, raising questions about journalistic responsibility. This article examines how Polish media navigate objectivity amid political and economic pressures in an era of epistemic accountability. Through interviews with editors-in-chief and senior editors, the study explores how objectivity is redefined, what deviations from neutrality are deemed legitimate, and how newsrooms negotiate ethical commitments, social responsibility, and editorial independence. Drawing on standpoint theory and hybrid journalism, the analysis identifies five editorial strategies: values-driven objectivity, strategic framing, selective pluralism, fact-based editorial discipline, and critical engagement. Unlike past studies on ideological divides, this research focuses on how editors balance objectivity with social responsibility, editorial independence, and diversity.